The crime of issuing a check without a balance A comparative analytical study - Nyan Jafar Hassan Ahmed; Sheelan Mohammed Sharif; Awesta Burhan Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
General commercial papers have an important role in economy. Commercial papers generally have an important function in the economic field to facilitate business and trade as well as transference of money and the tool of credit and instrument of full fulfillment. For this reason, the Iraqi legislator assigned in the third section, article 39 - 185 provision related to commercial papers in article 137 - 175 customizes the check material. Misconceptions in dealing with checks, whether in terms of issuing them as ordinary bonds or making the check a credit instrument, and its conflict with the primary function of check or issue of the check without balance. The new trade law included nee provisions for the regulation of the check in accordance with the basic function in article 549 of the Iraqi penal code 111 of 1969. The legislator dealt with the issue of the check without balance. Trust the check and manipulate it at the current card to protect the check, and survival of confidence to keep trust in the check; and for this reason, in our research the crime of drawing a check without the balance is a common crime, and there is a set of rules and provisions related to the check, such as the mandatory and optional conditions in the check. What are the penal provisions? In the case of conflict among laws, which law is applied? There is a set of jurisprudence and jurisprudence to apply the provisions of the articles related to this type of crime. And did the judiciary take the same direction as the legislator in the accountability of people who commit the crime or not? When a crime committed by the state or government institutions or when participate in the crime, what will be the consequences? Article 459 of the Iraqi penal code is applicable in these cases. And for the purpose of studying the subject if crime check without balance, the research has a section dedicated to introduction, and chapter one as well as the conclusion. The first topic is dedicated to the definition of commercial papers and their types. The second section is dedicated to the problems of the crime of drawing check without balance. And in the second part, the responsibility of the legal person for the crime the check was withdrawn without balance. Finally, the main conclusion and recommendations are reached by the researcher.